2022
DOI: 10.1371/journal.pgen.1009747
|View full text |Cite|
|
Sign up to set email alerts
|

WAPO-A1 is the causal gene of the 7AL QTL for spikelet number per spike in wheat

Abstract: Improving our understanding of the genes regulating grain yield can contribute to the development of more productive wheat varieties. Previously, a highly significant QTL affecting spikelet number per spike (SNS), grain number per spike (GNS) and grain yield was detected on chromosome arm 7AL in multiple genome-wide association studies. Using a high-resolution genetic map, we established that the A-genome homeolog of WHEAT ORTHOLOG OF APO1 (WAPO-A1) was a leading candidate gene for this QTL. Using mutants and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
87
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 42 publications
8
87
0
Order By: Relevance
“…The Wheat Aberrant Panicle Organization 1 (WAPO1) gene codes for an F-Box protein [44]. In wheat, the F-box proteins function as a component of the Skp1-Cullin1-F-box (SCF) complex that recognizes substrates to be ubiquitin tagged for degradation [75].…”
Section: Wheat Aberrant Panicle Organization-wapo1mentioning
confidence: 99%
See 1 more Smart Citation
“…The Wheat Aberrant Panicle Organization 1 (WAPO1) gene codes for an F-Box protein [44]. In wheat, the F-box proteins function as a component of the Skp1-Cullin1-F-box (SCF) complex that recognizes substrates to be ubiquitin tagged for degradation [75].…”
Section: Wheat Aberrant Panicle Organization-wapo1mentioning
confidence: 99%
“…At higher levels of WAPO1 expression, more spikelets were observed; however, the percent of infertile spikelets increased with the expression, such that the plants with the highest expression of WAPO1 were associated with a decrease in yield. WAPO1 contains two exons and one small intron, spanning approximately 1460 base pairs, and is predicted to translate into a 440 amino acid protein [44]. A single copy of WAPO1 exists on each of the three chromosomes from set seven with a relatively even, but low expression across all three genomes (Figure 5).…”
Section: Wheat Aberrant Panicle Organization-wapo1mentioning
confidence: 99%
“…WAPO1 on wheat chromosome arm 7AL was identified as the best candidate gene regulating spikelet number per spike based on a fine genetic map, a genome-wide association analysis, and the known functions of the orthologous APO1 gene in rice ( Kuzay et al, 2019 ; Voss-Fels et al, 2019 ). Since then, more robust evidence from numerous materials with various genetic backgrounds that were tested under different environments and from mutants and transgenic wheat ( Ma et al, 2019 ; Ding et al, 2021 ; Jones et al, 2021 ; Kuzay et al, 2022 ) has demonstrated that WAPO-A1 is the causal gene for the previously reported QTLs. WAPO-A1b in haplotypes such as Berkut had more than threefold higher transcript levels than WAPO-A1a with the 115-bp deletion and three SNPs in the promoter in haplotypes such as RAC875, suggesting that the reduced transcript level of WAPO-A1a was due to the 115-bp deletion and three SNPs ( Kuzay et al, 2019 ; Voss-Fels et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This would explain the low SPS observed for Soissons, carrying the early PPD-D1a allele, despite having the high-SPS WAPO-A1b allele, an observation mirrored for Fielder in comparison to Yitpi. WAPO-A1 native alleles on the other hand have not been reported to cause large changes in flowering time in field trials 25,45 and while transgenic expression delayed flowering, CRISPR and EMS mutants had no significant effects 27 . However, the WAPO-A1b allele has a larger effect on the number of SPS in the winter wheat NIAB MAGIC population (+2.1 SPS) compared to the spring wheat CSIRO MAGIC population (+1.1 SPS) and an epistatic interaction between WAPO-A1, VRN-D3, PPD-B1 and Qsn.csu-6B has been described 45 .…”
Section: Overexpression Of Wapo-a1 In Hexaploid Wheat Increases Spsmentioning
confidence: 94%
“…The WAPO-A1 gene has been proposed as the candidate gene for a major QTL for SPS on 7AL mapped in several populations [22][23][24][25][26] and the WAPO-B1 gene as a candidate for a smaller QTL for SPS on 7BL 22 . Recently, 27 Kuzay et al, 2022 demonstrated, using CRISPR-generated mutants and transgenic plants, the role of WAPO-A1 and WAPO-B1 in determining SPS in tetraploid wheat.…”
Section: Overexpression Of Wapo-a1 In Hexaploid Wheat Increases Spsmentioning
confidence: 99%